The Changes in Text Cohesion of Senior High School Students Measured by Coh‐Metrix as a Function of Grade Level - Wang, Mengjie (Journal of Theory and Practice of Social Science, 2023)
National English Curriculum Standards for General High School sets requirements for text cohesion and text cohesion is an essential component of English writing and English writing evaluation. However, previous studies explored text cohesion mainly from perspectives of college students, horizontal comparison and traditional tools. In this study, a corpus of 300 essays by grade level (senior one and senior three) are analyzed computationally by Coh‐Metrix to examine whether text cohesion improves as grade level rises. During the specific process, this paper aims to identify characteristics and discriminate differences between the text cohesion created by the two grades. The main instrument is Coh‐Metrix—a type of computational tool that offers over 200 measurements to quantify texts. This study mainly employs the measures under the category of referential cohesion, LSA and connectives of it to assess text cohesion. The results demonstrate that as the grade level increases, text cohesion gets better. Specifically, these students produce more noun overlap of adjacent sentences, argument overlap of adjacent sentences, noun overlap of all sentences, argument overlap of all sentences, stem overlap of all sentences, LSA overlap of adjacent sentences, LSA overlap of adjacent paragraphs, LSA overlap of given/new sentences all connectives and additive connectives.